Neuromuscular performance in the hip joint of elderly fallers and non-fallers - Morcelli, Mary Hellen [UNESP]; LaRoche, Dain Patrick; Crozara, Luciano Fernandes [UNESP]; Marques, Nise Ribeiro [UNESP]; Hallal, Camilla Zamfolini; Rossi, Denise Martineli; Goncalves, Mauro [UNESP]; Navega, Marcelo Tavella [UNESP] (Springer, 2016)
Backgrounds Low strength and neuromuscular activation of the lower limbs have been associated with falls making it an important predictor of functional status in the elderly. Aim To compare the rate of neuromuscular activation, rate of torque development, peak torque and reaction time between young and elderly fallers and non-fallers for hip flexion and extension. Methods We evaluated 44 elderly people who were divided into two groups: elderly fallers (n = 20) and elderly non-fallers (n = 24); and 18 young people. The subjects performed three isometric hip flexion and extension contractions. Electromyography data were collected for the rectus femoris, gluteus maximus and biceps femoris muscles. Results The elderly had 49 % lower peak torque and 68 % lower rate of torque development for hip extension, 28 % lower rate of neuromuscular activation for gluteus maximus and 38 % lower rate of neuromuscular activation for biceps femoris than the young (p < 0.05). Furthermore, the elderly had 42 % lower peak torque and 62 % lower rate of torque development for hip flexion and 48 % lower rate of neuromuscular for rectus femoris than the young (p < 0.05). The elderly fallers showed consistent trend toward a lower rate of torque development than elderly non-fallers for hip extension at 50 ms (29 %, p = 0.298, d = 0.76) and 100 ms (26 %, p = 0.452, d = 0.68). The motor time was 30 % slower for gluteus maximus, 42 % slower for rectus femoris and 50 % slower for biceps femoris in the elderly than in the young. Discussion Impaired capacity of the elderly, especially fallers, may be explained by neural and morphological aspects of the muscles. Conclusion The process of senescence affects the muscle function of the hip flexion and extension, and falls may be related to lower rate of torque development and slower motor time of biceps femoris.
Keywords: Accidental falls; Muscle strength; Dynamometer; Electromyography; Aging